A1.53 A novel pro-inflammatory B cell population in the rheumatoid synovium can be identified by expression of FCRL4. (31st January 2014) - Yeo, L; Lom, H; Juarez, M; Buckley, C; Filer, A; Raza, K; Scheel-Toellner, D
Abstract : Background and Objectives: The importance of B cells in the pathogenesis of rheumatoid arthritis (RA) is highlighted by the clinical effectiveness of rituximab. Potential mechanisms for B cells in driving disease processes include autoantibody production, antigen presentation and cytokine secretion. Our recent findings suggest a pro-inflammatory and destructive role for B cells via production of RANKL, TNF-α and IL-6. A memory B cell subset in tonsils which expresses Fc receptor-like 4 (FcRL4) has previously been found to produce RANKL. We sought to determine whether the RANKL-expressing B cells present in the RA synovium belong to this subset. Methods: Synovial fluid and peripheral blood cells from RA patients were analysed for B cell differentiation markers by flow cytometry. Synovial tissue samples from RA patients were assessed using immunofluorescence and immunohistochemistry. FcRL4 mRNA expression was determined in synovial samples from RA patients and uninflamed control subjects by real-time PCR. FcRL4+ and FcRL4- CD19 + B cells were sorted from synovial fluid using a MoFlo cell sorter. mRNA expression of 48 cytokines was determined using Taqman microfluidic cards. Results: FcRL4 expressing B cells were detected in the synovial fluid (median 14% of B cells) at a significantly higher frequency compared to peripheral blood (median 0.04%; p = 0.004). RANKL was significantly enriched in the FcRL4+ B cell population compared to the FcRL4- population. FcRL4+ B cells were predominantly switched memory B cells, expressing significantly higher levels of CD80, CD86, CD95, CD20 and CD11c than FcRL4- cells. Sorted FcRL4+ B cells expressed significantly higher mRNA levels of RANKL and TNF-α than FcRL4- B cells. FcRL4+ B cells expressing RANKL were present in synovial tissue, and were distributed under the synovial lining layer and in perivascular cuffs. FcRL4 mRNA was detected in synovium from RA patients but not uninflamed controls, and FcRL4 expression in RA synovium correlated positively with the degree of leukocyte infiltration. Conclusions: We have identified a novel pro-inflammatory subset of B cells in the RA synovium which expresses RANKL and TNF-α and shows considerable expression of co-stimulatory molecules indicating a potential pathogenic role in RA. As these cells express high levels of CD20 it is conceivable that their removal contributes to the anti-inflammatory clinical effect of rituximab.